Perancangan Sensor Kapasitor Dan Penggunaan Sensor Warna Sebagai Pendeteksi Tingkat Kematangan Biji Kopi Kawi Roasting Menggunakan Logika fuzzy Berbasis Arduino - Bahril Ilmid Nugroho; Azam Muzakhim; Lis Diana Mustafa (Politeknik Negeri Malang, 2021)
Coffee is one of the most popular drinks in Indonesia because of its taste and aroma. Coffee in its presentation has different types which are determined by the coffee beans maturity level during roasting, including light roast, medium roast and dark roast. Each of the three types of roasting profiles has a different level of moisture in the beans. The use of a roaster machine to determine the coffee beans maturity level often uses temperature and roasting time settings. Knowing the capacitance value in determining the roasting l evel is expected to increase the accuracy of the roasting level. In this study, a capacitor sensor consisting of two parallel copper plates was designed to determine the roasted coffee beans maturity level. The frequency value and color sensor in the system were used to determine the basic value of the classification of Kawi coffee beans maturity level in the fuzzy system. Based on the results, namely at a parallel cap acitor sensor distance of 2 cm, the oscilloscope readings of dark maturity have a frequency range between 201KHz - 213KHz, medium in the range 179KHz - 206KHz and light 178KHz - 200KHz. Meanwhile, the Arduino frequency counter readings at the dark maturity level in range of 204KHz - 234KHz, medium in range of 210KHz - 227KHz and light at 205KHz - 223KHz. The results of the maturity level classification of Kawi coffee beans with fuzzy values for dark < 43.50, 43.50 < medium < 174 and light > 174.